Assessment of new pressure-corrected design method for hypersonic internal waverider intake. (December 2022) - Musa, Omer; Huang, Guoping; Yu, Zonghan
Abstract: The osculating axisymmetric flows concept is an extension of the concept of the osculating cones for designing waveriders which is also utilized to design the three-dimensional internal waverider intake, where the three-dimensional flowfield is generated using slices of locally two-dimensional flow. However, this design methodology neglects the effect of cross-flow between the osculating planes, which causes lateral pressure gradients. Therefore, this article introduces and assesses a new pressure-corrected osculating axisymmetric flows design approach for the three-dimensional internal waverider intake. The new design concept adds the lateral pressure gradient correction into the original design concept using cross-flow velocities calculated by Euler's incompressible flow equation between the osculating planes. Thereafter, three-dimensional streamlines are formed instead of the osculating plane's two-dimensional streamlines. The new design procedure is presented in detail and then verified using wavecatcher intake with a circular shape that contains zero lateral pressure gradients. No geometry changes are found when the pressure-corrected wavecatcher intake is compared with the uncorrected wavecatcher intake. Moreover, four hypersonic wavecatcher intakes of semi-rectangular and rectangular entrance and exit shapes are designed with a design point of Mach number 6.0 and numerically studied to assess the new design approach. The results revealed that the pressure-corrected wavecatcher intakes exhibited better total pressure recovery, flow uniformity, Mach number, and kinetic energy efficiency than uncorrected wavecatcher intakes. While the impinged shockwave is attached to the intake's entrance, and the mass flow is completely captured in all designs. It is found that 38.49% and 30.36% of the exit area of the pressure-corrected wavecatcher intakes, and 35.68% and 28.37% of the exit area of the uncorrected wavecatcher intakes, have provided the combustor with air having a total pressure recovery above 0.7, respectively. Highlights: The osculating axisymmetric flows concept is modified to account for the cross-flow effect. A pressure-corrected concept that includes lateral pressure gradients effects is proposed. A design procedure is presented and pressure-corrected wavecatcher intakes are designed. The proposed method is assessed using six wavecatcher intakes via numerical analysis. It is found that the proposed concept enhances the total pressure recovery and uniformity.